Capacity Building for the Tourism Awareness Group (Pokdarwis) in Edu-Tourism Village Through the “Integrated Thematic Green Rural Development Model” in the Gunung Kawi Religious Tourism Area, East Java - Desti Nur Aini; Agung Winarno; Fitria Earlike Anwar Sani; M. Kharis (Faculty of Smart Technology and Engineering, Universitas Kristen Maranatha, Bandung, Indonesia, 2025)
The development of green rural tourism that offers the advantages of the natural environment and local culture is an interesting trend so that through the community service program, it is expected to build awareness and increase the technical capacity of tourism managers in maintaining environmental sustainability so that the tourism sector remains sustainable and competitive. The location of the community service is in Sumberdem Village, which is the area in the Wonosasi Sub-district in the Gunung Kawi region. The approach used was the initiation model in the form of integrated green rural development through the stages of needs identification, analysis, introduction of ideas, training, demonstration, and evaluation. Data collection on the success of the program was conducted through a closed questionnaire to obtain structured answers and interviews to explore more in-depth information related to the impact and effectiveness of the program. This program has produced a green tourism management model guidebook, which contains an introduction to green tourism, prerequisites for managers, implementation of SOPs, and good practices. The results of the post-training evaluation questionnaire showed an increase in the capacity of Pokdarwis administrators and members, especially those related to insight development, environmental awareness, and visitor management skills.